2022
DOI: 10.1002/adom.202200278
|View full text |Cite
|
Sign up to set email alerts
|

Highly Luminescent Copper(I) Halide Phosphors Encapsulated in Fumed Silica for Anti‐Counterfeiting and Color‐Converting Applications

Abstract: Os(II) complexes given the low price, minor environmental pollution, and abundant resource of copper. [1][2][3][4][5][6][7][8][9][10][11][12][13] Owing to the rich coordination chemistry of Cu(I) ions, their combination with organic and inorganic ligands often leads to a large structural diversity, ranging from discrete molecular 0D to 1D chains, and from 2D layers to extended 3D networks. [14][15][16][17][18] Generally, luminescent Cu(I) hybrid materials can be synthesized via the reaction of CuX with organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…It is well-known that tunable luminescence is very essential for various applications of Cu I hybrid materials. [38] Encouraged by the dual-emission luminescence performance, we then demonstrated this material application for LED. Firstly, without modulating various phosphors, WLED device can be constructed just through encapsulating the powder (mixing with 25 % polystyrene (PS)-methylbenzene solution) on a violet InGaN light chip (Figure 8a).…”
Section: Application In Wledsmentioning
confidence: 98%
“…It is well-known that tunable luminescence is very essential for various applications of Cu I hybrid materials. [38] Encouraged by the dual-emission luminescence performance, we then demonstrated this material application for LED. Firstly, without modulating various phosphors, WLED device can be constructed just through encapsulating the powder (mixing with 25 % polystyrene (PS)-methylbenzene solution) on a violet InGaN light chip (Figure 8a).…”
Section: Application In Wledsmentioning
confidence: 98%
“…It is worth exploring that the intensity of the TL spectra in the low‐temperature region (peak 1) is quickly reduced as the temperature increases, whereas the TL spectra intensity in the high‐temperature region (peak 2) slowly decreases and moves toward the high‐temperature region. In Figure 4D, the trap depth is analyzed using the initial ascent method, which assumes a constant concentration of carriers trapped in the low‐temperature side of the TL spectra, which can be expressed by the kinetic equation 9,37,45 : Itbadbreak=Aexp()EtKT$$\begin{equation}{I_t} = A\exp \left( {\frac{{ - {E_t}}}{{KT}}} \right)\end{equation}$$where It${I_t}$ is the intensity of TL spectra, A represents the constant, including the frequency factors, K is the Boltzmann constant, and Et${E_t}$ is trap depth. It is demonstrated that the trap depth variations range between 0.307 and 1.246 eV, and the detailed data are shown in Figure S13 and Table S4, where all the trap depths can be well fitted as straight lines by fitting, which proves the existence of two continuously distributed trap energy levels in the material (Figure 4D).…”
Section: Resultsmentioning
confidence: 99%
“…It is worth exploring that the intensity of the TL spectra in the low-temperature region (peak 1) is quickly reduced as the temperature increases, whereas the TL spectra intensity in the high-temperature region (peak 2) slowly decreases and moves toward the high-temperature region. In Figure 4D, the trap depth is analyzed using the initial ascent method, which assumes a constant concentration of carriers trapped in the low-temperature side of the TL spectra, which can be expressed by the kinetic equation 9,37,45 :…”
Section: LImentioning
confidence: 99%
See 1 more Smart Citation
“…1d, revealing a broadband absorption peak with a range of 300–500 nm, which can be seen in similar Cu( i ) metal halides. 7,14–16 The PL spectrum with an excitation wavelength of 420 nm demonstrates broadband emission centred at 527 nm. Note that the emission spectra obtained at different wavelengths (270 and 420 nm) and different temperatures (80 and 300 K) are almost identical (Fig.…”
mentioning
confidence: 99%